Foreign Experience in Land Use Management - A.M.Abdulloyev; SH.Y.Sattorov; M.V.Sulaymonov; SH.H.Abdualiyeva; A.B.Ochilov; T.A.Ismatov (Indonesian Journal of Innovation Studies, 2022)
This article discusses the current importance of databases and land databases in land resource management.